Вплив мікрохвильового випромінювання на стан антиоксидантної системи в тканинах перепелиних ембріонів та добового молодняку - Цибулін, Олександр; Tsybulin, Оlexandr (Східноєвропейський національний університет імені Лесі Українки, 2016)
У роботі на моделі перепелиного ембріона продемонстровано достовірний оксидативний ефект мікрохви- льового випромінювання, який проявлявся у вираженому зростанні рівня перекисного окиснення ліпідів і зниженні активності ключових ферментів антиоксидантної системи живих клітин. Long-term exposure of humans to low intensity radiofrequency electromagnetic radiation (RF-EMR) leads to a statistically significant increase in tumor incidence. Mechanisms of such the effects are unclear, but features of oxidative stress in living cells under RF-EMR exposure were previously reported. The aim of our study was to investigate the effect of microwave radiation on the state of the antioxidant system in the tissues of embryo and daily quail. Embryos of Japanese quails were exposed in ovo to extremely low intensity RF-EMR of GSM 900 MHz (14 мW/cm2) during 158–456 h discontinuously (48 c – ON, 12 c – OFF) before and in the initial stages of development. Significant oxidative effect of microwave radiation on the model of quail embryos was demonstrated. The effect was manifested in increased level of lipid peroxidation and decreased activity of key enzymes of antioxidant system.
Influence of Microwave Radiation on Antioxidant System in the Tissues of Embryos and Daily Quail.
Keywords: мікрохвильове випромінювання; антиоксиданти; оксидативний стрес; ембріогенез; мобільний телефон; microwave radiation; antioxidants; oxidative stress; embryogenesis; mobile phone